The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/pr9040595
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Disruption Properties of Essential Oils—A Double-Edged Sword?

Abstract: The emerging literature has suggested essential oils (EOs) as new possible weapons to fight antimicrobial resistance due to their inherent antimicrobial properties. However, the potential pharmaceutical use of EOs is confronted by several limitations, including being non-specific in terms of drug targeting, possessing a high cytotoxicity as well as posing a high risk for causing skin irritation. Furthermore, some EOs have been demonstrated to adversely affect the cellular lipid profiles and permeability of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 77 publications
(107 reference statements)
0
33
0
Order By: Relevance
“…However, it is known that gram-negative bacteria have an outer membrane, rich in lipopolysaccharides, which acts as a permeability barrier against hydrophobic molecules, hence it is expected that EOs are less effective against gram-negative than gram-positive bacteria. Nevertheless, it is worth noting that EOs could also be cytotoxic to eukaryotic cell membranes [52]. Therefore, further studies are needed with respect to both target and non-target organisms.…”
Section: Antimicrobial Activity Of C Japonica Eo In Food Industry and Human Diseasesmentioning
confidence: 99%
“…However, it is known that gram-negative bacteria have an outer membrane, rich in lipopolysaccharides, which acts as a permeability barrier against hydrophobic molecules, hence it is expected that EOs are less effective against gram-negative than gram-positive bacteria. Nevertheless, it is worth noting that EOs could also be cytotoxic to eukaryotic cell membranes [52]. Therefore, further studies are needed with respect to both target and non-target organisms.…”
Section: Antimicrobial Activity Of C Japonica Eo In Food Industry and Human Diseasesmentioning
confidence: 99%
“…There are many research studies demonstrating their biological benefits, including antioxidant, anti-inflammatory, anti-cancer, antimicrobial (antibacterial, antiviral, antifungal, and antiparasitic), analgesic, sedative, and wound healing [ 19 , 20 , 21 ]. With regard to the current antimicrobial resistance crisis, EOs have proven their efficiency by targeting microbial cell walls or membranes, cellular respiration processes, or quorum sensing mechanisms [ 19 , 24 ]. Nevertheless, despite their tremendous potential, EOs have a series of limitations associated with their increased hydrophobicity, volatility, lipophilicity, and oxidation susceptibility and decreased solubility and stability [ 21 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds may be combined with essential oils to improve their bioavailability. The hydrophobicity of essential oils enables a better partition of phenolic compounds within the lipids of the cell membrane and mitochondria, thereby increasing their permeability and ultimately leading to the release of intracellular constituents [227,228] and to interference with many biological processes [229]. Wang et al [230] showed that Colletotrichum gloeosporioides (Penz.)…”
Section: Effect Of the Combination Of Phenolic Compounds With Other Natural Products Or Conventional Fungicidesmentioning
confidence: 99%